Puppet Hizbul Wathan as a media to introduce and strengthen leadership character in elementary school students - Luqman Nul Hakim; Fitri Puji Rahmawati (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
Cultural degradation in children can manifest through the behavior of contemporary youngsters. Delinquent behavior is also prevalent in the school environment, including elementary schools. The purpose of this research is to describe the results of the design and expert assessment of the puppet Hizbul Wathan. The research type employed is qualitative research. The research design utilized is also qualitative research. Data collection techniques include observation, interviews, and documentation. The observation and interview techniques use question guidelines that will be observed and asked to sources. Data validity obtained by researchers involves triangulation, which includes both triangulation of techniques and triangulation of sources. The results reveal that the puppet Hizbul Wathan learning media is suitable for use in elementary schools for enhancing leadership character. This is supported by several stages of expert testing, including assessments from artists and teachers, individual trials involving students, and group trials encompassing both students and teachers, all of which received an average rating of 'very good.' Learning outcomes achieved with Hizbul Wathan shadow puppet learning media are superior. Consequently, the Hizbul Wathan shadow puppet learning media is more effective in improving learning outcomes and enhancing student leadership character.